2014
DOI: 10.1155/2014/383859
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofToxoplasma gondiiby PCR and Mouse Bioassay in Rodents of Ahvaz District, Southwestern Iran

Abstract: Toxoplasma gondii is obligate coccidian zoonotic parasite. Felidae family is definitive and wide ranges of warm-blooded vertebrates are intermediate hosts for the parasite. Rodents are measured as an important source of T. gondii infection for the definitive host. Thus, this study aimed to investigate Toxoplasm infection in rodents of Ahvaz district, southwest of Iran. A total of 100 rodents (73 Rattus norvegicus, 21 Rattus rattus, and 6 Mus musculus) were collected and studied by GRA6PCR and mouse bioassay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It should be mentioned that R. norvegicus is the most abundant rodent in southwest of Iran (73/100) and highest prevalence and rate of infection (4.1%, 3/73) allocate to this species which corresponds to previous investigations [9, 11]. The obtained results of amplifying 18s rRNA gene after sequencing were submitted to the DDBJ/GenBank under accession numbers AB986579 , AB986580 , and AB986581 and then compared with AB986578 as control.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It should be mentioned that R. norvegicus is the most abundant rodent in southwest of Iran (73/100) and highest prevalence and rate of infection (4.1%, 3/73) allocate to this species which corresponds to previous investigations [9, 11]. The obtained results of amplifying 18s rRNA gene after sequencing were submitted to the DDBJ/GenBank under accession numbers AB986579 , AB986580 , and AB986581 and then compared with AB986578 as control.…”
Section: Discussionmentioning
confidence: 72%
“…Also, annual average rainfall is approximately 230 mm. There is high density of rodents species and rat-man-domestic animals adjacency is remarkable in Ahvaz city [9, 11]. Rodents are additional reservoir for Cryptosporidium spp., mostly preyed on by cats and dogs, and, hence, could spread parasitic infections via other animals [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]. Another study of urban rodents from Iran shown that 6% of all collected specimens were DNA positive in brain tissue detected by PCR [26].…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas, Rattus norvegicus act as a reservoir of zoonotic pathogens, especially zoonotic parasites, and hold a connection to various important hygienic problems; they are also responsible for human morbidity and mortality, worldwide [7]. Many of these zoonotic parasites including Leishmania spp, Giardia spp, Toxoplasma gondii, Trichomonas vaginalis, and Cryptosporidium spp are assumed to be endemic in Rattus norvegicus populations around the world [8,9,10,11]. Currently, approximately seventy-nine species of rodents have been recognized in Iran; among these previously identified rodents, Rattus norvegicus have shown greater frequency in the urban area and occupied widespread habitats in cities [12].…”
Section: Introductionmentioning
confidence: 99%